Implications of a Social Movement against Racism for a More Inclusive Global Fashion Industry - Ranti, Munif Arif; Seniwati, Seniwati; Syahdan, Pusparida (Andalas Institute of International Studies UNAND, 2023)
Fashion and racism are complex issues with pressure for the industry to be more inclusive of racial differences. The Black Lives Matter movement has drawn attention to the issue of racism in the fashion industry and inspired social efforts to address it. Increased support for this cause has resulted in more entities contributing to eliminating racism in the industry through actions such as black model matter campaigns and the founding of The Kelly Initiative, which advocates for the diversity and inclusivity of the fashion industry. This research aims to examine the impact of social movements in combating racism and promoting equality in the global fashion industry. Qualitative methods are used with several theoretical frameworks, including racism, to show neglect, which results in discrimination, as well as global social movements, which are used to show forms of collective action in the form of protests that seek inclusive change in fashion. The results show that social movements can transform the fashion industry through rapid advances in diversity and inclusion through collective action. The implication is that it allows all parties to contribute to fashion without facing racial discrimination, thereby achieving diversity and inclusion.